PENGARUH METODE EKSTRAKSI SECARA INFUNDASI DAN MASERASI DAUN ASAM JAWA (Tamarindus indica L.) TERHADAP KADAR FLAVONOID TOTAL - , HANNY LUTHFINA FARDHANI, Prof. Dr. Suwijoyo Pramono, DEA, Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tamarind (Tamarindus indica L.) can be used as traditional medicine. The leaves rich in flavonoids which has function as antioxidant and has been researched could decrease cholesterol. The high level of flavonoids in tamarind leavesâ extract influenced by the extraction process. This study aims to determine the effect of the extraction method of maceration and infundation. This study used fresh tamarind leaves which were taken from Kecamatan Mergangsan, Daerah Istimewa Yogyakarta. Extraction process of infundation method used aquadest as solvent while maceration method used ethanol 96% (1:10). Fractination was performed with ethanol 96% and n-hexane. After getting thin-layer chromatography (TLC) profiles, the level of total flavonoids calculated. Samples which the level of total flavonoids was calculated were decoction extract (ED), maceration extract (EM), ethanolic fraction (FLE) and non nâhexane fraction (FTLH) with rutin as marker. Standard curve has been made from concentration series of 0,045